Studies of Rare Earth Polyphosphate Glasses of Composition [NaxM(1-x)/2aDy(1-x)/2aPO3]n - Seth, Gita; Agrawal, Anjana (Asian Journal of Chemistry, 2010)
Fusion technique was used for the preparation of derivatives of composition [NaxM(1–x)/2aDY(1-x)/2aPO3]n [where M1 = bivalent metal like Cu(II), Ca(II), Zn(II) and Mg(II) and X = 2/3 and 3/4 and a = valency of metal]. Compositions of these polyphosphate glasses were confirmed by their analysis for metals and phosphorus. The polymeric nature of all polyphosphate glasses was confirmed by determination of number average molecular weight (Mn). The characteristic frequencies in the IR spectra are supportive of the presence of polyphosphate indicative of the polymeric nature of these derivatives.